Solution proposed to a 2000 year old problem in oncology - Retsky, Michael (Henry Stewart Talks, 2019)
Primary cancer surgery, Systemic inflammation, Metastatic amplification, Perioperative inflammation as triggering origin of metastasis development, Hazards of relapse, Computer simulations and clinical observations, The linkage between wounding, immunology, inflammation and oncology, Ketorolac and the uses of perioperative NSAIDs